Hybrid Systems for Marine Energy Harvesting - Rosa-Santos, Paulo Jorge; Taveira Pinto, Francisco; López Gallego, Mario; Rodríguez Castillo, Claudio Alexis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Technologies to harvest marine renewable energies (MREs) are at a pre-commercial stage, and significant R&D progress is still required in order to improve their competitiveness. Therefore, hybridization presents a significant potential, as it fosters synergies among the different harvesting technologies and resources. In the scope of this Special Issue, hybridization is understood in three different manners: (i) combination of technologies to harvest different MREs (e.g., wave energy converters combined with wind turbines); (ii) combination of different working principles to harvest the same resource (e.g., oscillating water column with an overtopping device to harvest wave energy); or (iii) integration of harvesting technologies in multifunctional platforms and structures (e.g., integration of wave energy converters in breakwaters). This Special Issue presents cutting-edge research on the development and testing of hybrid technologies for harvesting MREs and intends to inform interested readers on the most recent advances in this key topic.